ANALISIS PERHITUNGAN KERUGIAN DAYA PADA LENDUTAN SERAT OPTIK DENGAN SIMULASI MATLAB - Joni Welman Simatupang; Faisal Syamsuri; Ria Bramasto; Fajar Choirul Anam; R. Hilary Yoga Ardanta (TESLA: Jurnal Teknik Elektro, 2022)
Bending is one of the causes of signal transmission loss through the electromagnetic wave medium in the optical fiber. There are two types of bendinglossess: microbending and macrobending. Both of them occur when the surface of the optical fiber cable experiences external pressure which causes deformation in the core of the optical fiber. Bending causes the loss of the optical transmission power affected by decreased light intensity, therefore the output ratio becomes degraded to the input one. This kind of condition assumed can be utilized for designing the optical fiber-based sensor by observing the response of the optical fiber against the external disturbances or stimulation.One example is the mechanical force that causes the deformation to the optical fiber. Based on the simulation result through the Matlab programming for macrobending loss, it was obtained that the highest power loss at 1.817×10-4 dB/mm on the 10mm bending radius for the 1650nm wavelength, and the lowest at 2.683×10-8 dB/mm on the 20mm bending radius for the 1250 nm wavelength. Meanwhile for microbending loss, it obtained the largest change of transmission coefficient at 59.070% for 100mm spacer length with applied mechanical force as large as 106 dynes or 10N, and the smallest change at 0.591% for 10mm spacer length with applied mechanical force as large as 105 dynes or 1N. These significant changes of the measured values show that the optical fiber, by simulation, is pretty responsive against the external stimulations, either on the macroscopic scale or the microscopic scale. So that based on its responsiveness, we can assume that optical fiber is most likely possible to be utilized in variousmodern fiber optic sensor for many applied technologiesABSTRAK:Lendutan atau bending merupakan salah satu penyebab kerugian transmisi sinyal melalui medium gelombang elektromagnetik berupa cahaya melalui pada serat optik. Terdapat dua jenis bending, yaitu macrobending dan microbending. Keduanya adalah tipe lendutan yang terjadi ketika permukaan serat optik mendapat tekanan eksternal yang menyebabkan terjadinya deformasi pada inti serat optik. Lendutan mengakibatkan berkurangnya daya transmisi optik dikarenakan berkurangnya intensitas cahaya, sehingga nilai keluarannya menjadi terdegradasi. Kondisi tersebut diasumsikan dapat dimanfaatkan untuk perancangan sensor berbasis serat optik dengan mengamati respon serat optik terhadap gangguan eksternal. Sebagai contoh berupa gaya mekanis yang menyebabkan serat optik terdeformasi. Berdasarkan hasil simulasi melalui Matlab untuk macrobending, diperoleh kerugian daya tertinggi sebesar 1.817 × 10-4 dB/mm pada radius bending 10 mm untuk panjang gelombang 1650 nm, dan terendah sebesar 2.683 × 10-8 dB/mm pada radius bending 20 mm untuk panjang gelombang 1250 nm. Sementara untuk microbending, diperoleh perubahan koefisien transmisi tertinggi sebesar 59.070% untuk panjang penyekat 100 mm dengan gaya mekanis sebesar 106 dyne atau 10 N, dan terendah sebesar 0.591% untuk panjang penyekat 10 mm dengan gaya mekanis sebesar 105 dyne atau 1 N. Perubahan nilai yang sangat signifikan tersebut menunjukkan bahwa serat optik secara simulasi cukup responsif terhadap stimulasi eksternal, baik dalam skala makro maupun mikro. Berdasarkan sifatnya yang cukup responsif, dapat disimpulkan bahwa serat optik sangat mungkin untuk dimanfaatkan dalam perancangan sistem sensor moderen untuk berbagai aplikasi teknologi.